Rapid Automation 2019
DOI: 10.4018/978-1-5225-8060-7.ch070
|View full text |Cite
|
Sign up to set email alerts
|

Towards Odor-Sensitive Mobile Robots

Abstract: Out of all the components of a mobile robot, its sensorial system is undoubtedly among the most critical ones when operating in real environments. Until now, these sensorial systems mostly relied on range sensors (laser scanner, sonar, active triangulation) and cameras. While electronic noses have barely been employed, they can provide a complementary sensory information, vital for some applications, as with humans. This chapter analyzes the motivation of providing a robot with gas-sensing capabilities and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Robotic olfaction (RO) is a recent filed of research that involves many important technological and scientific challenges [24][25][26][27][28][29]. It refers to the use of mobile robots in combination with a sensing technology to perceive gas release in the environment [30].…”
Section: Robot Olfactory Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Robotic olfaction (RO) is a recent filed of research that involves many important technological and scientific challenges [24][25][26][27][28][29]. It refers to the use of mobile robots in combination with a sensing technology to perceive gas release in the environment [30].…”
Section: Robot Olfactory Problemmentioning
confidence: 99%
“…A general and powerful extension in this research field suggested in different studies as a potential future development, is the adaptation of methodologies for the third spatial dimension and for augmenting the solution to a multirobot collaboration scheme. These improvements in many cases may help to reduce the time needed to cover a large area and improve at the same time the quality of the sampled data when a low-cost multisensory system is used [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Drones In the Gsl Applicationmentioning
confidence: 99%
“…CBRN related robotics has seen a swell of research interest in recent years, as recently summarised in Monroy and Gonzalez-Jimenez [2019], due to the ever increasing computational capabilities of small onboard chipsets and chemical sensors that can be easily fitted to mobile platforms including small UAVs. Coupled with their mobility to collect large amounts of data at any location, these systems are highly beneficial compared to the traditional approach of sparse static sensors running alongside complex CFD models that can take several days to resolve.…”
Section: State Of the Artmentioning
confidence: 99%
“…Portable, low-cost electronic noses (e-noses) based on an array of partially selective MOX sensors are widely used for gas sensing in many applications, including but not limited to landfill ( Perera et al, 2001 ; De Vito et al, 2011 ; Gębicki et al, 2014 ) and ship emission monitoring ( Yuan et al, 2020 ), chemical leakage detection in industrial sites ( Capelli et al, 2014 ; Bourne et al, 2020 ), early fire detection ( Young et al, 2003 ; Scorsone et al, 2006 ; Joseph et al, 2015 ), exploration of interested areas for emergency response or environmental monitoring ( He et al, 2019 ; Anyfantis et al, 2021 ), etc ( Monroy and Gonzalez-Jimenez, 2019 ; Burgués and Marco, 2020a ). In many real-world gas sensing related applications, gas detection comes as a fundamental task that recognizes the presence of gases by monitoring their concentration levels exceeding pre-defined thresholds.…”
Section: Introductionmentioning
confidence: 99%